Behçet Necatigil’in Şiirlerinin Söz-Eylem Kuramı Çerçevesinde İncelenmesi - Evin, Sema (Fatih Sultan Mehmet Vakıf Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2022)
Cumhuriyet Dönemi Türk edebiyatı gerek toplumsal gerek küresel açıdan birçok değişime ve dönüşüme tanıklık etmiştir; bu gelişmelere bağlı olarak Cumhuriyet Dönemi Türk şiiri de kendini, yeni kuramların, konu çeşitliliğinin ve farklı edebi toplulukların ortasında bulmuştur. Modern Türk şiirinin en yetkin isimlerinden Behçet Necatigil (1916-1979) böylesi bir ortamda, gelenekle bağını koparmadan, gelişmeleri yakından izleyen üslûp sahibi bir şair olarak karşımıza çıkmaktadır. Behçet Necatigil’in Şiirlerinin Söz-Eylem Kuramı Çerçevesinde İncelenmesi başlıklı çalışmamızda, Behçet Necatigil’in hem şair hem de Türk dili ve edebiyatı öğretmeni olması Türk dilinin kullanım olanaklarını en üst seviyedesomutlaştırması, tezimizin zeminini oluşturan Söz-Eylem Kuramı’nın Behçet Necatil’in örnek olarak belirlediğimiz şiirlerinde tespit edebilmemizi sağlamıştır. Behçet Necatigil’in konumuz sınırları içinde taşıdığı pek çok özellik, araştırmacılar için - bilhassa dilbilim alanında çalışan araştırmacılar-önem arz etmektedir. Tezimizde, XX. yüzyıl başlarında ilk olarak John Langshaw Austin (1911-1960) tarafından temeli atılan devamında Austin’in öğrencisi olan John Searle’ ün(d.1932) geliştirdiği Söz-Eylem Kuramı’nın özelliklerini belirlemeye çalıştık. Dilbilimin alt dallarından anlambilim ve edimbilimle ilgili kısaca bilgi vererek şair (gönderici) ile okur (alıcı) arasındaki etkileşimi “kuram”ın özellikleri çerçevesinde, Behçet Necatigil’in şiirlerinden örnekler vererek açıkladık. Tezimiz, önsöz, giriş ve sonuç bölümleri hariç üç bölümden oluşmaktadır. Çalışmamızın birinci bölümde, Söz-Eylem Kuramı’nın zeminini oluşturan gelişmelere, alana katkı sağlayan dilbilimcilere değindik. Söz-Eylem Kuramı’nın özelliklerini ve kavramlarını, açıklamaya çalıştık. İkinci bölümde, Behçet Necatigil’in sanatını oluşturan unsurları, şiirinin geçirdiği aşamaları ve dönemleri açıklamaya çalıştık; tezimizin üçüncü bölümünde ise Necatigil’in halk şiirinin özelliklerini yansıtan, tahkiyeli anlatımla örülmüş şiirlerine, hikâyeyi kısarak sözcüklerin çok anlamlılığından daha fazla yararlandığı şiirlerindeki derin yapıyı inceledik. Necatigil’in modern şiire yaklaştığı, sözcüklerin arasını açarak farklı denemeler yaptığı, çok yönlü okumaya elverişli özgün şiirlerine örnek verdik, farklı dönemlerden seçtiğimiz şiirler üzerinde “kuram”ın temelini oluşturan “düzsöz” “edimsöz”“etkisöz” özelliklerini göstermeye gayret ettik.

Turkish literature of the Republican Period has witnessed many changes and transformations, both socially and globally; Depending on these developments, the Turkish poetry of the Republican Period also found itself in the middle of new theories, diversity of topics and different literary communities. Behçet Necatigil (1916-1979), one of the most competent names of modern Turkish poetry, appears before us as a poet with a style who follows innovations closely without breaking his ties with tradition. In our thesis, we will examine Necatigil's poems within the framework of Speech-Act Theory. The reason why we want to examine the Speech-Act Theory, which forms the basis of our thesis, on Behçet Necatigil's poems is that Necatigil's qualities and his poems have features suitable for the subject of our thesis. It is important for researchers - especially for researchers working on linguistics -that Behçet Necatigil knowing very well the possibilities of using the Turkish language and embodying these possibilities at a highest level by applying them to his poems. We will try to explain the Speech-Act Theory, which was first laid by John Langshaw Austin (1911-1960) at the beginning of the 20th century, and later developed by Austin's student John Searle (b.1932). In order to better understand the theory, . By giving brief information about semantics and pragmatics, which are sub-branches of linguistics, we will explain the message between the poet/speaker (sender) and the reader/listener (receiver) by basing the interaction on the characteristics of the theory, by giving examples from Behçet Necatigil's poems. Our thesis consists of three parts, excluding the preface, introduction and conclusion. In the first part of our study, we briefly mentioned the developments that formed the basis of Speech-Act Theory, the theories that pioneered the Speech-Act Theory, and linguists. We tried to explain the features and concepts of Speech-Act Theory. In the second part, we tried to explain the elements that make up Behçet Necatigil's art, the stages and periods of his poetry; In the third part of our thesis, we gave examples of Necatigil's poems that reflect the characteristics of folk poetry, knitted with narrative expression, and his poems in which he shortens the story and in his poems makes more use of the polysemy of words and we examined that the deep structure of his poems. We gave examples of Necatigil's poems, in which the poet approaches modern poetry, makes different experiments by opening a space between the words, we gave examples of the authentic poetry which is adequate to versalite reading, on the poems we selected from different periods, we tried to show the features of locutionary, illocutionary and perlocutionary.
Examination of Behçet Necatigil’s Poetry Within the Frame of Speech-Act Theory
Keywords: Behçet Necatigil; Söz-Eylem Kuramı; John Langshaw Austin; John Searle; Dilbilim; Speech-Act Theory; John Langshaw Austin; John Searle; linguistics